Pengaruh Akuntabilitas, Transparansi, Partisipasi Masyarakat dan Pemberdayaan Masyarakat Terhadap Pencegahan Kecurangan - Bella Dwi Gina Pitaloka; Anita Carolina; Rian Abrori; Habi Bullah (Journal of Sharia Economics, Banking and Accounting, 2025)
The tourism sector is currently an important part of the economic development strategy directed at the concept of sustainable tourism. One such tourism is mangrove ecotourism which requires the implementation of good governance and open community participation to avoid fraud. Therefore, this study aims to examine the effect of implementing accountability and transparency as well as the sustainability of community participation and empowerment in all operational activities on fraud prevention. The sample obtained in this study was 161 respondents from 4 mangrove tours based on purposive sampling method which was analyzed using multiple linear regression tests. The results showed that accountability has a positive effect on fraud prevention, while transparency, community participation and community empowerment have no effect on fraud prevention